Speaking from among the bones [large type] : a Flavia de Luce novel - Bradley, Alan, 1938- (Bradley, Alan, 1938- Flavia de Luce mystery., 2013)
Eleven-year-old amateur detective and ardent chemist Flavia de Luce is used to digging up clues, whether they're found among the potions in her laboratory or between the pages of her sisters' diaries. What she is not accustomed to is digging up bodies. Upon the 500th anniversary of St. Tancred's death, the English hamlet of Bishop's Lacey is busily preparing to open its patron saint's tomb. Nobody is more excited to peek inside the crypt than Flavia, but what she finds will halt the proceedings.